GWAS-Identified Common Variants With Nonalcoholic Fatty Liver Disease in Chinese Children. Issue 5 (May 2015) - Shang, Xiao-Rui; Song, Jie-Yun; Liu, Fang-Hong; Ma, Jun; Wang, Hai-Jun
ABSTRACT Objectives: Three genome-wide association studies were previously done for nonalcoholic fatty liver disease (NAFLD) among individuals of Western countries and identified several genetic variants associated with NAFLD. The study aimed to identify whether 7 GWAS-identified common variants (GCKR rs780094, PDGFA rs343064, FDFT1 rs2645424, COL13A1 rs1227756, EHBP1L1 rs6591182, NCAN rs2228603, and PNPLA3 rs738409) were associated with NAFLD in Chinese children. Methods: This case-control study recruited 1027 Chinese children of age 7 to 18 years, including 162 children with NAFLD and 865 children without NAFLD. Anthropometric measurements, alanine transaminase (ALT) detection, liver ultrasound examination, and genotyping of 7 variants were performed. Results: The G-allele of PNPLA3 rs738409 was associated with NAFLD (odds ratio [OR] 1.55, 95% confidence interval 1.13–2.11, P = 0.006) and moderate-to-severe steatosis (OR 3.77, 95% confidence interval 1.78–7.98, P = 0.001) adjusted for age, sex, and BMI standard deviation score. In addition, we found each G-allele of rs738409 increased ALT level by 1.09 IU/L (P = 0.011). Subjects carrying 10 or more risk alleles of 7 variants had an OR of 4.76 (P = 0.025) for NAFLD compared with subjects carrying 3 or fewer risk alleles. Conclusions: The PNPLA3 rs738409 G-allele was associated with NAFLD and ALT level in Chinese children. It had stronger association with moderate-to-severe steatosis. Children carrying 10 or more risk alleles of 7 variants were susceptible for NAFLD.